If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 7 = 69 Reorder the terms: 7 + 2x = 69 Solving 7 + 2x = 69 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 2x = 69 + -7 Combine like terms: 7 + -7 = 0 0 + 2x = 69 + -7 2x = 69 + -7 Combine like terms: 69 + -7 = 62 2x = 62 Divide each side by '2'. x = 31 Simplifying x = 31
| 3y-2=2/7 | | 5h-6=24 | | 2x-11x+5=0 | | s=69120/35000 | | 8w+9=-31 | | 3x+18y-(2x+y)+9=12 | | y+8=4-3y | | 23+4x=2(3*3) | | (x+3)+(2x+1)=10 | | 10x^3-25x^2-15x=0 | | 6x=10-4x | | 19/57= | | 30/41= | | 5=3x+43 | | 27/54= | | 3=6x+83 | | 4b^2-33b-27= | | 15/35= | | 3=6x+3 | | 8-9x=2x | | X^2+7=32 | | 4x+2-15=21 | | 4(n-1)=6n-12 | | 2x-5+6x+7= | | 3t-t+12-5=22 | | 4(-1)=6n-12 | | 1.5x-2=10 | | 125a^3+216=0 | | 0.666x+1=x-4 | | x^3-8x^3+8x^2+32x-44=0 | | 4a-1=-19-2a | | x-3=0.5x-2 |